Cost-effectiveness analysis of toripalimab for metastatic or recurrent triple-negative breast cancer - Shao, Jiangbo; Zhan, Cuiping; Jin, Chunxiang; Jin, Ying (Frontiers in Oncology, 2024)
Background: Toliparibizumab in combination with nab-paclitaxel (T+N) has excellent efficacy inmetastatic or recurrent triple-negative breast cancer (TNBC), but the optimal choice of sequence of therapy is unclear given the trade-offs between quality of life and cost. Cost-effectiveness analyses can quantify these tradeoffs, leading to more informed decisions. Our objective was to assess the societal cost-effectiveness of the T+N regimen for metastatic or recurrent TNBC.: Clinical data were extracted from a multicenter, randomized, double-blind trial, TORCHLIGHT (NCT04085276). Patients were randomized into the T+N group or placebo plus nabpaclitaxel (P+N) group. 531 patients from 53 study locations were randomly assigned (T+N, n=353; P+N, n=178) into intend to treat (ITT) population; 200 and 100 patients, respectively had programmed death protein 1 (PD-L1) positive TNBC. A Markov model was established with a 21day cycle length. Costs were acquired from local hospitals, effect parameters included qualityadjusted life year (QALY) and incremental cost-effectiveness ratio (ICER).